Younger patients with chronic myeloid leukemia do well in spite of poor prognostic indicators: results from the randomized CML study IV - Kalmanti, Lida; Saussele, Susanne; Lauseker, Michael; Proetel, Ulrike; Mueller, Martin C.; Hanfstein, Benjamin; Schreiber, Annette; Fabarius, Alice; Pfirrmann, Markus; Schnittger, Susanne; Dengler, Jolanta; Falge, Christiane; et al. (Annals of Hematology, 2014)
Since the advent of tyrosine kinase inhibitors, the impact of age on outcome of chronic myeloid leukemia (CML) patients has changed. We therefore analyzed patients from the randomized CML study IV to investigate disease manifestations and outcome in different age groups. One thousand five hundred twenty-four patients with BCR-ABL-positive chronic phase CML were divided into four age groups: (1) 16-29 years, n = 120; (2) 30-44 years, n = 383; (3) 45-59 years, n = 495; and (4) >=60 years, n = 526. Group 1 (adolescents and young adults (AYAs)) presented with more aggressive disease features (larger spleen size, more frequent symptoms of organomegaly, higher white blood count, higher percentage of peripheral blasts and lower hemoglobin levels) than the other age groups. In addition, a higher rate of patients with BCR-ABL transcript levels >10 % on the international scale (IS) at 3 months was observed. After a median observation time of 67.5 months, no inferior survival and no differences in cytogenetic and molecular remissions or progression rates were observed. We conclude that AYAs show more aggressive features and poor prognostic indicators possibly indicating differences in disease biology. This, however, does not affect outcome.
EVALuna2:25675